Flavonoid biosynthesis controls fiber color in naturally colored cotton - Liu, Hai-Feng; Luo, Cheng; Song, Wu; Shen, Haitao; Li, Guoliang; He, Zhi-Gang; Chen, Wen-Gang; Cao, Yan-Yan; Huang, Fang; Tang, Shou-Wu; Hong, Ping; Zhao, En-Feng; et al. (PeerJ, 2018)
The existence of only natural brown and green cotton fibers (BCF and GCF, respectively), as well as poor fiber quality, limits the use of naturally colored cotton (Gossypium hirsutum L.). A better understanding of fiber pigment regulation is needed to surmount these obstacles. In this work, transcriptome analysis and quantitative reverse transcription PCR revealed that 13 and 9 phenylpropanoid (metabolic) pathway genes were enriched during pigment synthesis, while the differential expression of phenylpropanoid (metabolic) and flavonoid metabolic pathway genes occurred among BCF, GCF, and white cotton fibers (WCF). Silencing the chalcone flavanone isomerase gene in a BCF line resulted in three fiber phenotypes among offspring of the RNAi lines: BCF, almost WCF, and GCF. The lines with almost WCF suppressed chalcone flavanone isomerase, while the lines with GCF highly expressed the glucosyl transferase (3GT) gene. Overexpression of the Gh3GT or Arabidopsis thaliana 3GT gene in BCF lines resulted in GCF. Additionally, the phenylpropanoid and flavonoid metabolites of BCF and GCF were significantly higher than those of WCF as assessed by a metabolomics analysis. Thus, the flavonoid biosynthetic pathway controls both brown and green pigmentation processes. Like natural colored fibers, the transgenic colored fibers were weaker and shorter than WCF. This study shows the potential of flavonoid pathway modifications to alter cotton fibers’ color and quality.
Keywords: Fiber color; Naturally colored cotton; Flavonoid biosynthesis; Fiber quality; Transcriptome analysis; RNA interference